Description Of Primigravid Pregnant Women's Behavior In Dealing With Emesis Gravidarum During The Covid-19 Pandemic - Eti Noviatul Hikmah; Qararim Makin (Sean Institute, 2023)
Study results conducted at the Health Center Mpunda obtained data from 10 primigravida pregnant women who experienced emesis during the COVID-19 pandemic. There were 4 people with positive behavior in facing emesis gravidarum during the COVID-19 pandemic and 6 people with negative behavior in dealing with emesis gravidarum during the COVID-19 pandemic. Research This is descriptive quantitative research.Method study This is a descriptive usage.In research, a sample of up to 10% of the population, or 42 people, is used, with the sampling technique being random.study This is based on secondary data from notes taken at the Mpunda health center during the COVID-19 pandemic about a number of primigravida mothers who experienced emesis gravidarum.Study This was done using instruments such as a questionnaire containing statements (positive and negative) about behavior and dealing with emesis gravidarum during the COVID-19 pandemic, which totaled 15 questions. The majority of primigravida pregnant women at the Mpunda health center are between the ages of 17 and 25, accounting for 92.86% of respondents; distribution education accounts for 76.19% of respondents. Category No Work, which is as high as 64.29% of respondents, and the behavior of primigravida pregnant women experiencing emesis during the COVID-19 pandemic at the Primary care Mpunda in 2021, which is as high as 100%.